APPLICATION OF GAME-BASED SIMULATION IN “SYSTEM ANALYSIS” COURSES - S. E. Shchepetova; A. I. Satdykov (Высшее образование в России)
The application of the game-based education technologies in a modified version of “the beer distribution game” on a number of disciplines devoted to the study of the system approach in economics has proven its effectiveness. This variant of the game has been updated by the professors of the Financial University. The gamification of education process basing on supply chain modeling made it possible to demonstrate clearly to students how the structure of the system determines its behavior and influences the behavior of individual components, as well as to focus their attention on the main system characteristics and features of socio-economic systems. Gaming technologies served as a starting point to analyze and summarize the data collected by students during the game, to acquire the skills of formalizing practical situations and building models of complex systems. Also they served to study the behavior of different systems by exploring their models, and for later learning of theoretical material based on the “drawing knowledge” principle and in-depth study of issues related to various aspects of system’s functioning. The gamification of the education process made it possible to increase the students’ involvement into subject being studied, to understand better the theory of system thinking and to develop practical research competences.